RESPON PETANI PADI SAWAH TERHADAP PROGRAM BUDIDAYA SISTEM JAJAR LEGOWO DI KECAMATAN CIBALIUNG KABUPATEN PANDEGLANG - Munajat, Arby; Budiawati, Yeni (CV. Era Digital Nusantara, 2022)
The purpose of this study was to find the effect of the response of paddy rice farmers to the jajar legowo cultivation program in Cibaliung Subdistrict, Pandeglang Regency. In this study using a survey method because it collects information from respondents using a questionnaire / questionnaire. While the research design used is descriptive analysis and quantitative analysis. The samples used were 38 respondents which were calculated using the Slovin formula and data analysis methods using regression analysis performed using the help of IBM SPSS 21.0 software.Based on the results of the analysis using the help of IBM SPSS 21.0 software, it is known that the influence of farmer response and the role of extension agents on the Jajar Legowo cultivation program uses the regression equation = 3.828 - 0.420X1 + 0.790X2 + 1.175X3 e. The value of the multiple correlation coefficient (R) = 0.953 which means that the relationship of Attitudes, Knowledge, Skills, to the Cultural Program in the Legowo teaching system is very strong, while the coefficient of determination (Kd) = 90.7% means that the influence of Attitude, Knowledge, Skills indicates , for the rice cultivation program in the jajar legowo system, while the remaining 9.3% was influenced by other factors not included in this study. And from the results of the t test (Partial) it is known that tcount> t table, so Ho is rejected and Ha is accepted, this means that the variable Attitudes, Knowledge, Skills, have an influence on the rice cultivation program jajar legowo system, F_ (count)> F_table, then Hο is rejected and Ha is accepted, meaning that there is an influence between attitudes, knowledge and skills together on the Jajar Legowo system cultivation program.